The Knowledge and Attitude about Diarrhea of Mothers of Students Attending an Elementary School in a Suburban Area in Istanbul - SAVE, DİLŞAD; KARAVUŞ, MELDA; HIDIROĞLU, SEYHAN (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: Diarrhea is one of the main cause of morbidity and mortality among children age under 5 years in Turkey though diarrheal disease control program has been performing and death ratio due to diarrheal disease under 5 years has been decreasing year by year in Turkey. This study is undertaken to evaluate knowledge, attitude and practice of mothers about childhood diarrheal diseases in a suburban area. Methods: This descriptive study was carried out in a primary school in a suburban area of Istanbul. One hundred and forty four mothers of children included accepted in the study with response rate of 85%. A questionnaire form was applied for data collection. Epi-Info programme was used for statistical analysis. In addition to the descriptive statistical methods, for the comparison of qualitative data a chi-square test was used. Results: In our study, the percentage of mothers who could define diarrhea correctly was 40%. Abdominal pain and watery defecation were the main signs which the mothers understand their children have diarrhea. Most of the mothers indicated that microbes as the cause of diarrhea. One of every two mothers stated that they would take their children to the doctor as they notice their child has diarrhea. Among the homemade treatments we asked, Potatoes cooked in boiling water and banana were the most frequent answers. Only one of mothers mentioned about using drugs at home for diarrhea and percentage of hearing about ORS was 21.5%. Eleven percent of mothers mentioned they believed to decrease liquid intake would be an effective practice in the treatment of diarrhea. Education level was very influential about knowledge and attitude about diarrheal disease. Conclusion: This study reveals the importance of continuous health education of mothers as well as the need for raising their status especially schooling in communities. Circulating of correct information is also important as well as educating population.
Keywords: Childhood diarrhea; Mother; Knowledge; Istanbul; Turkey; MANAGEMENT; DISEASE